Deliberative Decision-Making on the Norwegian County Social Welfare Board: The Experiences of Expert and Lay Members. Issue 1 (1st January 2017) - Skivenes, Marit; Tonheim, Milfrid
Abstract : This article examine the entire population of expert and lay decision-makers on the Norwegian County Social Welfare Board, with 57% responding (n = 1598), asked whether they experience being fully informed about the facts in the case; are equal partners in the decision-making team, and if their arguments are taken seriously. Findings show they were highly satisfied with the proceeding and their role in it, and they positively highlighted the judge's role in the decision-making process. However, expert and lay persons are not provided with documents in a timely manner, and some lay members felt subordinate to the other decision-makers.